Development of Electronic Modules Based on Critical Thinking Skills on Vibration, Waves, and Sound Materials for Junior High School Students - Leni Marlina*; Gelby Pradina Paramitha; Ida Sriyanti (Universitas Syiah Kuala, 2022)
Electronic learning resources are needed in accordance with the demands of basic competencies in learning and can be used by teachers and students as a means of independent learning at home or at school. This study aims to develop an electronic module on the material of vibration, waves and sound that is valid and practical. The Rowntree development model used consists of three stages, namely planning, development and evaluation stages. At the evaluation stage, the researcher used the Tessmer evaluation stage, which consisted of the self-evaluation, expert review, one-to-one evaluation, and small group evaluation stages. The research subjects were students of class VIII.2 SMP N 1 Prabumulih. The research instrument used was observation, student needs questionnaire, expert validation questionnaire and student perception questionnaire. The data analysis technique used walkthrough and questionnaire methods. The resulting product is an electronic module of vibration, wave and sound material using the Flip PDF Professional program. The results of the research show: 1) the development of an electronic module based on critical thinking skills has been carried out through a development procedure that includes 3 stages. 2) the acquisition of the research results obtained content validation of 4.50 (strong valid), content validation of critical thinking skills of 4.61 (strong valid), design validation of 4.72 (strong valid), and language validation of 4 .50 (strong valid). So, the total average of the results of the content validation assessment, the content of critical thinking skills, design, and language is 4.60 including the